Anti-angiogenic and anticancer effects of baicalein derivatives based on transgenic zebrafish model. Issue 15 (15th August 2018) - Jiang, Xueyang; Zhou, Junting; Lin, Qinghua; Gong, Guiyi; Sun, Haopeng; Liu, Wenyuan; Guo, Qinglong; Feng, Feng; Qu, Wei
Graphical abstract: Abstract: Angiogenesis leads to tumor neovascularization by promoting tumor growth and metastatic spread, therefore, angiogenesis is considered as an attractive target for potential small molecule anticancer drug discovery. Herein, we report the structural modification and biological evaluation of baicalein derivatives, among which compound42 had potent in vivo anti-angiogenic activity and wide security treatment window in transgenic zebrafish model. Further, 42 exhibited the most potent inhibitory activity on HUVEC proliferation, migration and tube formation in vitro . Moreover, 42 significantly inhibited growth of human lung cancer A549 cells and weak influence on human normal fibroblast L929 cells. The present research demonstrated that the significant anti-angiogenic and anticancer effects, which provided the supportive evidence for42 could be used as a potential compound of cancer therapy.